Peningkatan Hasil Belajar Ilmu Pengetahuan Sosial Melalui Model Interaktif Berbasis Media Peta di Kelas V UPTD Sekolah Dasar Negeri 9 Merawang - Sari Dafia; Vika Martahayu; M Iqbal Arosyad (Lembaga Pengembangan Kinerja Dosen, 2024)
The aim of this study is to improve students' academic achievement through the use of map media in Social Science subjects. The research method used is qualitative, with a sample of 21 fifth-grade students from Sekolah Dasar Negeri 9 Merawang. This study was conducted in two cycles, with each cycle consisting of planning, implementation, observation, and reflection stages. In the first cycle, conducted over two meetings, the number of students who achieved the target mastery criteria was below 85 percent. Based on the results of this learning process, the researcher caried out the second cycle over two meetings, which showed an improvement in learning outcomes and an increase in the number of students achieving mastery. The number of students who achieved mastery in the Social Science subject was 19 out of 21 students. This indicates that the implementation of interactive learning model using map media can improve student learning outcomes, aligning with the motivation of students and teachers to encourage the achievement of mastery in the class.